Generalization Lags behind Learning on an Auditory Perceptual Task - Wright, Beverly A. (Society for Neuroscience, 2010)
The generalization of learning from trained to untrained conditions is of great potential value because it markedly increases the efficacy of practice. In principle, generalization and the learning itself could arise from either the same or distinct neural changes. Here, we assessed these two possibilities in the realm of human perceptual learning by comparing the time course of improvement on a trained condition (learning) to that on an untrained condition (generalization) for an auditory temporal-interval discrimination task. While significant improvement on the trained condition occurred within 2 d, generalization to the untrained condition lagged behind, only emerging after 4 d. The different time courses for learning and generalization suggest that these two types of perceptual improvement can arise from at least partially distinct neural changes. The notably longer time course for generalization than learning demonstrates that increasing the duration of training can be an effective means to increase the number of conditions to which learning generalizes on perceptual tasks.